Transforming E-waste plastics into biohybrid composite materials - Siaputra, Harvin (Nanyang Technological University, 2023)
Electronic waste (e-waste) production has become an urgent environmental issue, with an estimated 74.7 million metric tons expected by 2030. One of the major constituents of e-waste is Acrylonitrile Butadiene Styrene (ABS). On the other hand, diatoms, which contribute to a significant fraction of global oxygen production, have siliceous frustules, and can produce natural oils. In this study, we upcycled ABS from computer keyboard waste by refabricating the plastic into a porous scaffold and incorporating diatoms (Amphora coffeaeformis and Melosira nummuloides) into the scaffold. Formation of a biohybrid composite (D- ABS) was achieved through dissolution and salt leaching, followed by diatom seeding. Combined results from fluorescence microscopy imaging of chlorophyll a, PrestoBlue assay and scanning electron microscopy (SEM) show that the diatoms were able to proliferate in the ABS scaffold. The presence of silica frustules in the D-ABS porous structure was confirmed by thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). Furthermore, biolipids were successfully extracted using ethanol and approximately 14-45 μg of biolipids could be obtained from a single block of D-ABS composite. Culture optimization results suggest that the growth rate of the studied diatoms in D- ABS did not change significantly with different degrees of hydrophobicity of the ABS plastic surface and different light intensities. Furthermore, dynamic culture conditions involving continuous spiraling of the ABS scaffolds resulted in overall higher proliferation rates than static culture conditions in a well plate. Mechanical testing results show that D-ABS, containing the siliceous frustules, exhibited higher specific compressive modulus as compared to a blank porous ABS scaffold. Lastly, an overall net negative carbon footprint of 8982 pg could be achieved by a single block of D-ABS. Overall, these findings support the concept of using D-ABS as a promising approach for upcycling e-waste into high modulus materials, with added value in biofuel production and CO2 fixation, opening new possibilities for sustainability applications.